Peningkatan Hasil Belajar Siswa Pada Pelajaran PKNYang Mencerminkan Perilaku Harga Diri Melalui Metode Bermain Peran Di Kelas III Sekolah Dasar - Fitria Kumala Sari (Jurnal Family Education, 2021)
This research begins with the discovery of facts that are less satisfactory in learning PKN, namely still low student learning in SDN 25 JTT. In this case the learning process has not fully involved students, as well as the lack of use of media in the process of learning in the classroom that causes students less active and submitted material is not well received by students. to overcome these problems, then used the role playing method in learning PKN with material behavior that reflects self-esteem for students class III SDN 25 JTT Padang Timur